2016
DOI: 10.1016/j.tiv.2016.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic responses to 405nm light exposure in mammalian and bacterial cells: Involvement of reactive oxygen species

Abstract: Light at wavelength 405 nm is an effective bactericide. Previous studies showed that exposing mammalian cells to 405 nm light at 36 J/cm(2) (a bactericidal dose) had no significant effect on normal cell function, although at higher doses (54 J/cm(2)), mammalian cell death became evident. This research demonstrates that mammalian and bacterial cell toxicity induced by 405 nm light exposure is accompanied by reactive oxygen species production, as detected by generation of fluorescence from 6-carboxy-2',7'-dichlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(105 citation statements)
references
References 46 publications
4
96
1
4
Order By: Relevance
“…For this purpose, an assay for imaging collagen deposition on the culture substrate was established. [33] H 47Y<R did not show EGFP fluorescence after 24 h, which may be due to degradation because of lack of functional activity over time (Figure 5b). Hsp47 −/− cells incubated with H 47Y<R , H 47KDEL or EGFP did not show any fluorescence signal, whereas cells incubated with H 47N showed a clear fluorescence corresponding to collagen production (Figure 5b).…”
Section: Controlled Light Exposure Allows Spatial Regulation Of Collamentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, an assay for imaging collagen deposition on the culture substrate was established. [33] H 47Y<R did not show EGFP fluorescence after 24 h, which may be due to degradation because of lack of functional activity over time (Figure 5b). Hsp47 −/− cells incubated with H 47Y<R , H 47KDEL or EGFP did not show any fluorescence signal, whereas cells incubated with H 47N showed a clear fluorescence corresponding to collagen production (Figure 5b).…”
Section: Controlled Light Exposure Allows Spatial Regulation Of Collamentioning
confidence: 99%
“…Hsp47 −/− cells were incubated with the different Hsp47 variants for 3 h. Then the medium was exchanged and cells were cultured for further 24 h, fixed, and stained with Col1 Antibody for imaging deposited collagen type I on the culture substrates. [33] Cells at the exposed areas showed significant higher collagen deposition (Figure 5a). H 47N and light exposed H 47Y<ONBY showed EGFP fluorescence located at the ER, indicating that the recombinant protein delivered was still present intracellularly after 24 h ( Figure 5).…”
Section: Controlled Light Exposure Allows Spatial Regulation Of Collamentioning
confidence: 99%
“…; Ramakrishnan et al . ). We are undertaking further studies to elucidate the role of σ B in the response of L. monocytogenes to visible light stress.…”
Section: Resultsmentioning
confidence: 97%
“…Similar studies from other investigators suggested the presence of both porphyrins and flavins in A. actinomycetemcomitans (Cieplik et al, 2014; Fyrestam et al, 2015), porphyrins, flavin adenine dinucleotide (FAD), and nicotinamide adenine dinucleotide (NADH) in MRSA (Biener et al, 2017), porphyrins in P. gingivalis ( Fyrestam et al, 2015; Yoshida et al, 2017), porphyrins in S. cerevisiae (Fyrestam et al, 2015), and porphyrins (a mixture of coproporphyrin I, coproporphyrin III, and PpIX) in Helicobacter pylori (Battisti et al, 2017a; Battisti et al, 2017b) according to the spectroscopic or chromatographic analyses. Some other studies provided the evidence that the cytotoxicity of aBL to microbes is mediated by the aBL-induced production of ROS (Cieplik et al, 2014; Galbis-Martinez et al, 2012; O’Donoghue et al, 2016; Ramakrishnan et al, 2016; Yoshida et al, 2017). …”
Section: Mechanism Of Action Of Antimicrobial Blue Lightmentioning
confidence: 99%